x-4(x-3)+7=6-(x-4)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Solve `x -4(x - 3) = 6 - (x - 4).`

First distribute -4 on the left side of equation and distribute (-) on right side of equation.

`x - 4x + 12 + 7 = 6 - x + 4`

Now combine like terms on each side.

`-3x + 19...

See
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Get 48 Hours Free Access

Solve `x -4(x - 3) = 6 - (x - 4).`

First distribute -4 on the left side of equation and distribute (-) on right side of equation.

`x - 4x + 12 + 7 = 6 - x + 4`

Now combine like terms on each side.

`-3x + 19 = -x + 10`

Add x to each side to remove x from right side.

`-3x + x + 19 = -x + x + 10`

`-2x + 19 = 10`

Subtract 19 from each side to isolate x.

`-2x + 19-19 = 10 - 19`

`-2x = -9`

Divide both sides by -2 to isolate x.

`(-2x)/(-2) = (-9)/(-2)`

`x = 9/2`

The solution is x = `9/2`  or 4.5.

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

Solve multiplication and parenthesis first.

`x-4x+12+7=6-x+4`

Add x to both sides, so that all x terms are on the same side.

`x-4x+x+12+7=6+4`

Subtract 12+7 to both sides, so that all the constants are on the same side.

`x-4x+x=6+4-12-7`

Simplify each side.

`-2x=-9`

Divide both sides by -2

`x=(-9)/-2`

Therefore x=4.5

Approved by eNotes Editorial Team